Barbuda
1 online resource
Keywords: "This volume explores a range of themes including impacts of climate change, resilience, sustainability, indigeneity, cultural genocide, disaster capitalism, preservation of biodiversity, and environmental degradation. Focusing on the island of Barbuda in the West Indies, it shares critical insights into how climate change is reshaping our world. The book examines how climate has changed in the Caribbean over different spatial and temporal scales and how varying natural and anthropogenic factors have shaped Barbuda's climatic and cultural history. It highlights projections of 21st century climate change for the Caribbean region and its likely impacts on Barbuda's coastal ecosystems, potable groundwater resources and heritage. With essays by researchers from the United States, Canada, Caribbean, and Europe, this volume straddles a range of disciplines such as include archaeology, anthropology, paleoclimatology, environmental sciences, science education, and Traditional Ecological Knowledge (TEK). Drawing on interdisciplinary and transdisciplinary approaches that explore the intersection of natural and social systems over the longue durée, the volume will be of interest to scholars, researchers and students of ethnography, social anthropology, climate action, development studies, public policy, and climate change"--